Stimulasi Video Untuk Bermain Peran dan Diskusi Sebagai Upaya Meningkatkan Hasil Belajar - Yusminar Yusminar (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
The use of video films of struggle can provide insight and encouragement to internalize the struggle so that it stimulates students to get more information about historical figures and events. Teachers no longer need to dominate learning activities, so students are fully given the opportunity to become subjects in learning. To improve the quality of student learning processes through video stimulation of struggle and the application of role playing methods followed by discussions on social studies subjects. This research was carried out in Odd Semester SMP N 6 Kota Metro, there were 30 students. The procedure of implementing the class action research. The researcher concludes that the use of video films of the struggle to maintain independence provides stimulation to students to act according to the existing role script. Internalization of the struggle spirit of the video by students has encouraged students' interest in learning to understand efforts to maintain the struggle for independence more deeply. The output of the internalization is an increase in average social studies learning outcomes, and student assessment of the quality of the learning process that is getting better.